Ear biometrics in 2D and 3D localization and recognition - Prakash, Surya; Gupta, Phalguni; SpringerLink (Online service). (Singapore Springer Singapore, 2015)
This book presents the state-of-the-art techniques and recent research progress on Ear Biometrics. Among the various physiological traits, the reasons for the ear to gain much attention in recent years are many folds. It has been found to be a reliable biometrics for human verification and identification. Ears are remarkably consistent and unlike face, it does not change shape with different expressions or age, and remain fixed in the middle of the side of the head against a predictable background. The book contains figures, tables and plots to illustrate the techniques in an easy and lucid manner. The book also provides an extensive literature on the subject, where readers have the benefit of receiving all the relevant material at one place in a very comprehensive manner. This book caters students, academics, researchers, practitioners who are interested in the field of Ear Biometrics and its applications in face recognition and security.
Introduction -- Ear Detection in 2D -- Ear Recognition in 2D -- Ear Detection in 3D -- Ear Recognition in 3D -- Fusion of Ear with Other Traits.
Electronic reproduction.
Keywords: Biometric identification; Electronic books